PENGARUH SELF EFFICACY TERHADAP PERILAKU MENYONTEK SISWA KELAS X AKUNTANSI SMK MANDIRI PONTIANAK - Anisa Rindiyani; Endang Purwaningsih; Husni Syahrudin (Universitas Tanjungpura, 2019)
AbstractThis study aimed to determine whether there is an effect of self efficacy on cheating behavior of the X Accounting class student in SMK Mandiri Pontianak. The form of this research was quantitative research with the type of research ex-postfacto. The sample in this study was the Accounting X class of SMK Mandiri Pontianak, which amounted to 47 students. Data was collected by questionnaires that have been tested for validity and reliability. The data analysis technique used was a simple linear regression test with the help of the SPSS version 16.0 program. The results of this study indicated that the level of self-efficacy of students in X Accounting class in general was in the moderate category shown from the percentage of research results 14.89% of students in the low category, 70.21% of students in the medium category, and 14.89% students in the high category. While cheating behavior of student in X Accounting class in general was in the medium category indicated by the percentage of research results, 17.02% of students in the low category, 61.70% of students in the medium category, and 21.28% of students in the high category. There was a negative influence between self efficacy on cheating behavior of students with a regression equation Y = 33,877 - 0,649X. The results of hypothesis testing compared to significance value of 0.05, It can be seen that the significance value of 0,000 < 0.05 that means (H0) is rejected and (Ha) is accepted, means that it had a influence between self efficacy on cheating behavior in X Accounting Class SMK Mandiri Pontianak.Keywords: Self Efficacy, Cheating Behavior